PROPERTIES OF INTRACELLULAR MAGNETITE CRYSTALS PRODUCED BY DESULFOVIBRIO MAGNETICUS STRAIN RS-1 - Pósfai M.; Arató B.; Moskowitz B.M.; Schüler D.; Flies C.; Bazylinski D.A.; Frankel R.B. (My University, 2006)
Desulfovibrio magneticus strain RS-1 is an anaerobic sulfate-reducing bacterium. Cells form intracellular nanocrystals of magnetite but are only weakly magnetotactic. In order to understand the unusual magnetic response of this strain, we studied magnetite crystals within cells grown with fumarate and sulfate. Many cells grown under either condition did not form magnetic crystals while others contained only 1 to 18 small (~ 40 nm) magnetite-containing magnetosomes. Bulk magnetic measurements of whole cells showed a superparamagnetic-like behavior, indicating that many of the magnetite crystals are too small to have a permanent magnetic moment at ambient temperature. The temperature of the Verwey transition is lower (~ 86 K) than of magnetite from other magnetotactic strains, likely indicating partial oxidation of magnetite into maghemite. As a result of the small size and small number of magnetite magnetosomes, the magnetic moments of most cells grown anaerobically with fumarate or sulfate are insufficient for magnetotaxis. In addition to intracellular magnetite, in some cultures another iron oxide, hematite, formed on the surfaces of cells. The hematite grains are embedded in an extracellular polymeric material, indicating that the crystals likely resulted from a biologically-induced mineralization process. Although the hematite particles appear to consist of aggregations of many small (5 to 10 nm) grains, the grains have a consensus orientation and thus the whole particle diffracts as a single crystal. The aligned arrangement of nanoparticles within larger clusters may reflect either a templated nucleation of hematite crystallites in an extracellular organic matrix, or result from a self-assembling process during the crystallization of hematite from ferric gels or ferrihydrite. © 2006 Elsevier B.V. All rights reserved.
Keywords: DESULFOVIBRIO MAGNETICUS; HEMATITE; MAGNETIC PROPERTIES; MAGNETITE; MAGNETOTAXIS